Alcaloides e glicosídeo flavonoídico de Waltheria viscosissima A. St. Hil - Malvaceae - Rolim, Yngred Mangueira (2015)
The tradition of consumption of medicinal plants is one of the oldest practices of humanity and in the Brazilian scenario plants play an important role in folk medicine, not only for its food character, but also for its healing properties, whether for scientific grounds or by popular beliefs, knowledge of its chemical constituents, pharmacological activities and mechanism of action are open for proving the efficacy and its safe use. The Waltheria viscosissima A. St. Hil. Is a species belonging to Malvaceae family popularly known as viscosa malva. Listed in popular medicine to expectorant action, antitussive, anti-hypertensive, maturativa of tumors and for the treatment of ulcers. The phytochemical study of the phase ethyl acetate ethanol extract partitioning of Waltheria viscosissima A. St. Hil. and the phases obtained from the alkaloids gear through column chromatographic techniques led to the isolation of three substances: tilirosídeo (Wv-1), a mixture of waltheriona wlatheriona A and B (Wv-2). The structural identification of these substances were performed by spectroscopic methods using nuclear magnetic resonance IR and 1H and 13C, with the aid of single- and two-dimensional techniques, as well as by comparisons with literature data.